2018
DOI: 10.21071/pbs.v0i6.10785
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical Scent Detection Dogs: Would They Pass as a Health Technology?

Abstract: Biomedical scent detection dogs identify the scent profiles of diseases, such as cancer, diabetes or pathogenic micro-organisms.  What the field of biomedical scent detection has been lacking, however, is the assessment of the method from the point of view of a health technology. All health technologies undergo a thorough evaluation of safety, clinical effectiveness and costs, as well as ethical, social, organizational and legal evaluations in some cases. Passing these regulatory controls is a pre-requisite be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…The limit of detection for canines is at concentrations of one part per trillion, which is three orders of magnitude more sensitive than currently available instruments [ 12 ]. Consequently various studies have shown dogs‘abilities to detect with high rates of sensitivity and specificity [ 13 ] infectious and non-infectious diseases and conditions, such as different types of cancer [ 14 ], malaria [ 15 ], bacterial infections caused by e.g. Clostridium difficile or mastitis causing pathogens [ 16 , 17 ], hypoglycaemia in diabetics [ 18 ], and virus infections in cell cultures [ 12 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The limit of detection for canines is at concentrations of one part per trillion, which is three orders of magnitude more sensitive than currently available instruments [ 12 ]. Consequently various studies have shown dogs‘abilities to detect with high rates of sensitivity and specificity [ 13 ] infectious and non-infectious diseases and conditions, such as different types of cancer [ 14 ], malaria [ 15 ], bacterial infections caused by e.g. Clostridium difficile or mastitis causing pathogens [ 16 , 17 ], hypoglycaemia in diabetics [ 18 ], and virus infections in cell cultures [ 12 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a medical device or health technology requires an approval by national health organizations before permission for usage is granted. For such approval, ethical, social, organisational, and legal aspects are assessed alongside technological, economic and safety aspects, as well as clinical effectiveness [5].…”
Section: Discussionmentioning
confidence: 99%
“…Routinely, dogs nowadays are predominantly deployed for the identification of explosives, drugs, currencies, people, endangered animal species and parasites [4]. In recent years, medical scenting dogs have been trained to detect different medical conditions, but this area of work is still relatively in its infancy [5]. The use of odour detection as a diagnostic tool is of increasing interest in recent [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The limit of detection for canines is at concentrations of one part per trillion, which is three orders of magnitude more sensitive than currently available instruments 12 . Consequently various studies have shown dogs’ abilities to detect with high rates of sensitivity and specificity 13 infectious and non-infectious diseases and conditions, such as different types of cancer 14 , malaria 15 , bacterial infections caused by e.g. Clostridium difficile or mastitis causing pathogens 16,17 , hypoglycaemia in diabetics 18 , and virus infections in cell cultures 12,19 .…”
Section: Introductionmentioning
confidence: 99%